Biochemical criteria of toxicity of therapy with high doses of methotrexate in children with osteosarcoma - A. M. Strizhevskaya; E. G. Golovnya; A. Z. Dzampaev; V. N. Baykova (Успехи молекулярной онкологии)
Methotrexate (Mtx) is a cytotoxic drug from the group of antimetabolites, folic acid antagonists. High-dose (HD) Mtx in pediatric oncology are used for the treatment of osteosarcoma (OS), and other types of tumors. This therapy has allowed to achieve a five-year relapse-free survival rates up to 80 % in patients with OS. However, the high toxicity of Mtx is a serious constraint in achieving the maximum therapeutic effect, which in most cases poses the occurrence of side effects in patients on various organs and systems. Treatment should be under strict laboratory monitoring, primarily therapeutic drug monitoring the concentration of Mtx in serum.246 children (boys – 125, girls – 121) aged 5 to 16 years with osteosarcoma (mean age 12.2 years) who were treated in N.N. Blokhin Russian Cancer Research Center from 2006 to 2013. Patients were conducted from 1 to 8 courses HD Mtx at a dose of 8 or 12 g/m2 , administered within 4 h of infusion on the background of alkaline prehydrate. Leucovorin was administered intravenously, every 6 hours, starting 24 h from the start of the Mtx infusion. 1137 courses of HD Mtx were conducted with FPIA method (analyzer TDx/Flx, Abbott, USA). The technique of monitoring of homocysteine (Hcy) in the blood serum by analyzer Vitros 5/1FS (Johnson & Johnson, USA) during the entire course of high-dose Mtx was tested. In groups calculated pharmacokinetic parameters Mtx were tested: area under the pharmacokinetic curve (MtxAUC), clearance of methotrexate (ClMtx), the elimination half-life (T1/2 ) and the total time of excretion (Ttotal). Normal excretion of Mtx was revealed at 1050 courses Mtx, corresponding to the following values: 4 h – 1109 ± 283 μmol/l; 24 h – 4,67 ± 0,95 μmol/l; 42 h – 0,38 ± 0.16 µmol/l; 48 h – less than 0,23 ± 0.04 µmol/l; 72 h of 0.07 ± 0,03 µmol/l; 96 h of 0.03 ± 0.01 µmol/l. At 87 courses identified delayed Mtx excretion, accounting for 7.6 % of all courses. In all measured parameters: hourly concentration of Mtx, Ttotal, MtxAUC, Clmtx, T1/2 , is obtained statistically significant differences between normal and delayed Mtx excretion. Patients in group of delayed excretion of methotrexate were characterized by the development of hepatotoxicity, there were also observed 4 cases of the occurrence of acute renal failure.Monitoring of biochemical parameters (alanine aminotransferase, aspartate aminotransferase, lactate dehydrogenase) also revealed differences between the two groups – hepatotoxicity directly depended on MtxAUC, ClMtx and Ttotal, and the amplitude changes in activities of enzymes from course to course by increasing the number of course decreased.Our developed methodology of monitoring of Hcy in serum during the course of HD Mtx revealed that Hcy metabolic interconnected with Mtx – the higher the concentration of Mtx, the greater the amount of Hcy released into the blood. Hcy has a close metabolic relationship with Mtx – it can serve as a marker of the efficiency of suppression of the transformation of folates. During slow excretion of Mtx Hcy significantly increased in the blood, which also suggests that it can serve as a marker of pharmacodynamic effects of HD Mtx.